Tanggung Jawab Orang Tua dalam Perspektif Hadis: Analisis Tematik atas Kasus Kekerasan Ibu Tiri terhadap Anak Tiri - Muhammad Amzad; Baiq Intan Amalia Rahmadani; Safa Anzila Madaniah (JOURNAL SAINS STUDENT RESEARCH, 2026)
This study examines the responsibility of parents from the perspective of hadith, motivated by the case of TR's stepmother violence against her stepson, Nizam Savei (12 years old), in Sukabumi which led to the victim's death in early 2026. The research uses a qualitative approach with the type of library research and thematic method (maudhu'i), through four stages of analysis: al-jam'u (collection of hadiths), al-tasnif (classification), al-tahlil (analysis of sanad and matan), and al-istinbath wa al-tathbiq (conclusion and contextual application). Primary data sources include hadiths from the al-sittah pole and case documentation from KPAI. The results of the study found that the act of persecution was a serious violation of the principles of ri'ayah, mas'uliyyah, la dharara wa la dhirar, and the absence of rahmah in family relations based on the hadith kullukum ra'in wa kullukum mas'ulun 'an ra'iyyatihi (HR. Bukhari no. 893 and Muslim no. 1829). Key findings confirm that child protection responsibilities in reconstituted families are multi-layered: stepmothers are bound by de facto custody obligations, while biological fathers retain unfettered parental responsibilities despite changes in family structure. This research contributes to filling the academic gap related to the distribution of parenting responsibilities in the reconstituted family from a hadith perspective.